Asian Mega-Deltas Initiative builds learning alliance to address climate change issues in the Mekong Delta - Bernardo, Eisen (CGIAR System Organization, 2022)
To form a learning alliance that has an interest to address climate-related issues in the Mekong Delta of Cambodia, the CGIAR Initiative on Securing the Food Systems of Asian Mega-Deltas for Climate and Livelihood Resilience ( AMD ) conducted a workshop to build a network of diverse stakeholders in the provinces of Takeo and Prey Veng in Cambodia.